Introduction to applied econometrics analysis / by R. F. Wynn and K. Holden - "Wynn, R. F." (London, 1974)
Applied econometric analysis is used across many disciplines and in many branches of economics. Increasingly, data is becoming more readily available and software has become more powerful, enabling the analysis of numerous economic phenomenon. This textbook shows how econometric methods relate to applied econometric analysis and provides an introduction to the specification and uses of econometric models.
Keywords: Economics